Relationship between caries, body mass index and social class in Spanish children - Teresa Almerich-Torres; José María Montiel-Company; Carlos Bellot-Arcís; José Manuel Almerich-Silla (Elsevier, 2017)
Objective: To determine the association between caries, body mass index (BMI) and social class in child population of the Valencia region (Spain) at 6, 12 and 15 years, and study. Methods: In a cross sectional study of 1326 children aged 6 (n = 488), 12 (n = 409) and 15 years (n = 433) who took part in the 2010 Oral Health Survey of the Valencia region, the ICDAS II criteria were employed for diagnosing and coding all the teeth examined. The quantitative BMI values on a continuous scale were grouped into 3 categories (normal weight, overweight, obese) based on a table adjusted for age and gender. The highest-ranking occupation of the parents was taken to indicate the social class of the child. Results: The mean BMI was 17.21 at 6 years, 21.39 at 12 years and 22.38 at 15 years. No significant differences in caries indexes (DMFT or dft) by degree of obesity stratified by social class were found in any of the age groups studied. There was no significant correlation between BMI and DMFT-dft in any of the age groups. Conclusions: Obesity is not associated with dental caries in schoolchildren of this population